Time and process in ancient Judaism - Stern, Sacha (Littman library of Jewish civilization (Series), 2003)
This illuminating study is about the absence of time as an entity in itself in ancient Judaism, and the predominance instead of process in the ancient Jewish world-view. Evidence is drawn from a complete range of Jewish sources from this period.